Synthesis and characterization of [Ru@Ge12]3-: an endohedral 3-connected cluster - Espinoza-Quintero, G; Duckworth, JCA; Myers, WK; McGrady, JE; Goicoechea, JM (American Chemical Society, 2014)
The 12-vertex endohedral cluster [Ru@Ge12](3-) reveals an unprecedented D2d-symmetric 3-connected polyhedral geometry. The structure contrasts dramatically with the known deltahedral or approximately deltahedral geometries of [M@Pb12](2-) (M = Ni, Pd, Pt) and [Mn@Pb12](3-) and is a result of extensive delocalization of electron density from the transition-metal center onto the cage.